PENINGKATAN KETERMPILAN MENULIS CERPEN DENGAN MENGGUNAKAN MEDIA LIRIK LAGU PADA PESERTA DIDIK KELAS XI MIPA1 SMA NEGERI 1 KALASAN - Meisy Candra; Aris Daryono; Denik Wirawati (LPPM Universitas Widya Dharma, 2023)
This study aims to find out whether the use of song lyric can improve students' short story writing skills and to identify effective teaching strategies in using song lyric as inspiration in writing short stories. The research method used in this study was Classroom Action Research (PTK) which lasted for 2 cycles. The subjects of this study were students of class IX MIPA 1, academic year 2022/2023, which consisted of 36 students. The research instrument used was an observation sheet (observation). Technical data analysis of this research uses descriptive qualitative and quantitative analysis. Based on the results of research on the pre-cycle, cycle 1, and cycle 2, it was found that there was an increase in short story writing skills starting from the pre-cycle, cycle 1, and cycle 2, with average score 67.7; 78.4; an 84.7addition, based on the results obtained in this study, it is known that the implementation of using favorite objects has an effect on improving the short story writing skills of class XI MIPA 1 students. Keywords: Writing Skills, Favorite Objects, Short Stories